2008
DOI: 10.1021/pr0705136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Multistage Gas-Phase Fragmentation Behavior of Phosphoserine- and Phosphothreonine-Containing Peptides

Abstract: The increasing use of multistage tandem mass spectrometry (MS/MS and MS (3)) methods for comprehensive phosphoproteome analysis studies, as well as the emerging application of in silico spectral intensity prediction algorithms in enhanced database search analysis strategies, necessitate the development of an improved understanding of the mechanisms and other factors that affect the gas-phase fragmentation reactions of phosphorylated peptide ions. To address this need, we have examined the multistage collision-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
196
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(215 citation statements)
references
References 59 publications
18
196
1
Order By: Relevance
“…Our explanations are consistent with a recent report [28] in which the magnitude of the neutral loss of phosphoric acid was found to be highly dependent on the proton mobility of the precursor ion for both phosphoserine-and phosphothreonine-containing peptides. In this study [28], peptides with internal phosphoryla- tion sites were examined, and it was claimed that a charge-remote ␀-elimination reaction does not predominantly occur.…”
Section: Fragmentation Pathwaysupporting
confidence: 93%
See 1 more Smart Citation
“…Our explanations are consistent with a recent report [28] in which the magnitude of the neutral loss of phosphoric acid was found to be highly dependent on the proton mobility of the precursor ion for both phosphoserine-and phosphothreonine-containing peptides. In this study [28], peptides with internal phosphoryla- tion sites were examined, and it was claimed that a charge-remote ␀-elimination reaction does not predominantly occur.…”
Section: Fragmentation Pathwaysupporting
confidence: 93%
“…In this study [28], peptides with internal phosphoryla- tion sites were examined, and it was claimed that a charge-remote ␀-elimination reaction does not predominantly occur. In our study, however, peptides with N-terminus phosphorylation sites were examined and the dephosphorylation was not through charge-remote mechanism since the N-terminus charge was spatially close to the elimination sites.…”
Section: Fragmentation Pathwaymentioning
confidence: 99%
“…This mechanism has been shown to be inconsistent with newer labeling data and CID-MS 3 investigation of product ions. A more likely mechanism involves proton-induced elimination with neighboring participation of amino [56] or amide groups [57] from the N-terminal site of the phosphoserine residue, as recently reviewed [58]. Obviously, none of these mechanisms can apply to the elimination of phosphoric acid from deaminated serine residues in the z ions, which have vinylic α-hydrogen atoms and are missing the N-terminal functional groups.…”
Section: Mechanisms For Z-ion Dissociationsmentioning
confidence: 99%
“…Collectively, these results have revealed that peptides decorated with labile modifications often are not well behaved under low-energy MS/MS conditions. For example, facile loss of phosphoric acid from the side chains of serine-and threoninephosphorylated peptides often limits the available sequence-specific information contained in associated MS/MS spectra [17,18]. Interestingly, recent reports [19,20] suggest that higher energy, or "triple quadrupole like," MS/MS can provide improved sequence analysis, particularly for phosphorylated peptides.…”
mentioning
confidence: 99%